The Evaluation of the Vector System in Removal of Carious Tissue - Mine Yildirim; Figen Seymen; Nurullah Keklikoglu (International Journal of Dentistry)
The aim of this study was to evaluate the Vector system in comparison to the conventional technique in cavity preparation. Four extracted primary teeth with no restorations and similar fissure carious lesions and four permanent teeth extracted for orthodontic reasons were used. Class I preparations were made provided that the caries depth remained within the dentin limits. Two teeth were treated with an aerator, the other two had carious tissue removed with the Vector system. Prepared cavities were evaluated with scanning electron microscopy for the surface roughness of the dentine and enamel and for the carious tissue removal efficiency. This pilot study determined that it is possible to remove carious tissue and perform cavity preparation with the Vector system. According to this preliminary evaluation of surface quality, a cavity prepared with the Vector treatment system, allows for a slicker floor, and a more regular enamel-dentine line than that prepared with an aerator. However, the Vector system requires a longer treatment time which we believe may be a negative point, especially for young patients.